Cidade e identidade: São José dos Campos, do peito e dos ares - Almeida, Valéria Zanetti de (2008)
The present work has tried to tackle a common speech among São José dos Campos' s residents: the city's lack of identity. As the speech is something that is culturally and historically built, the understanding strictly demands an analysis of the past of the city. The mechanisms that had supposedly affected the identification supports of the residents were researched. The first idea was that if the speech wants a production of proposition, the city is able to hold the space of such production. Therefore, we have proposed to read the speeches that the city produced historically in order to sustain identities. We read about its spaces, its symbols and signs, its architecture, its photographs, printed sources and forms used to endorse representations. We have evidenced a text with a redundant language. Even though São José dos Campos's residents think it is difficult to identify marks linked to the city's memory, the space has created conditions for the residents to certify their industrial vocation. The power of this reference slowly erases, amidst the urban scenery, the elements of past references, more precisely of a time when São José dos Campos's economy was linked to a sanative past. The fading of the identification marks connected to the past has weakend the memory and mutilated the identity. The fact is that identities are not built without memories